A Healthy Lifestyle (Stt) And Its Constituent Components - Yuldashev Ikromjon; Mallaboev Farhod (Genius Journals, 2022)
A healthy lifestyle is reflected in the physical culture, the future of the younger generation of the president, his level of physical culture, his ownership, in other words,all performances concerning the children of the nation, the country, a number of his works, manuals, brochures
Keywords: Physical Development, Healthy Lifestyle , Theoretical Knowledge